2016
DOI: 10.1016/j.athoracsur.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Factors Associated With Hospital Readmission After Pulmonary Lobectomy

Abstract: Readmission is a frequent event after pulmonary lobectomy and is strongly associated with preoperative demographic factors and comorbidities. Resources and services should be directed to patients at risk for readmission and multicomponent care pathways developed that may circumvent the need for repeat hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 17 publications
9
34
1
1
Order By: Relevance
“…Finally, we did not collect information on the specific reasons why some patients received supportive care only for their recurrence. Functional decline and decreased quality of life after lung cancer surgery may have limited treatment options for some patients [4648] while others may have refused cancer-directed therapy. Functional status and patient treatment preferences are important areas for future research on patterns of care for recurrent lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not collect information on the specific reasons why some patients received supportive care only for their recurrence. Functional decline and decreased quality of life after lung cancer surgery may have limited treatment options for some patients [4648] while others may have refused cancer-directed therapy. Functional status and patient treatment preferences are important areas for future research on patterns of care for recurrent lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10,13 On the other hand, similar to previously reported series, our results confirm that male gender, pre-existing comorbidity, lack of private insurance and geographic area of patient residence remain important preoperative characteristics associated with increased risk of readmission. 13,18 The current series is the first within the literature to report that lower income level and surgery at a non-academic/research facility are additional significant preoperative factors associated with readmission.…”
Section: Commentmentioning
confidence: 94%
“…In 2016, a study analyzing California, Florida and New York state inpatient databases identified that male gender, government insurance, and COPD significantly increase the risk of readmission following lobectomy. 18 …”
Section: Commentmentioning
confidence: 99%
“…Prior review of the ACS NSQIP database revealed an overall 30-day readmission rate for thoracic operations of 11.1% [11]. Although prior studies have outlined postoperative characteristics, including readmission, after open and thoracoscopic resections, they have not examined related, unplanned readmissions specifically [12]. Our study represents the largest multiple institutional analysis of related, unplanned readmissions after thoracoscopic versus open anatomic lung resection for primary lung cancer.…”
Section: Commentmentioning
confidence: 96%